2012/13年の夏に起こった昭和基地近傍の南極氷床表面の顕著な融解現象 - 平沢, 尚彦 (2016)
This paper investigates a prominent melting event of the Antarctic ice-sheet surface near Syowa station occurred in 2012/13 summer. We had seen scattering of many ice-pieces on the way of travel from Dome Fuji station (77.5S, 40E, 3810 m a.s.l.) to Syowa station (69S, 40E, 22 m a.s.l.). In the 2012/13 summer, we had two extreme events, both of which may generate the ice-pieces scattering. During one of them, rainfall was observed at Syowa station, which was the first time after the previous rainfall nine years ago. During the other, very high surface air temperature (SAT), 8.6C, was observed at Syowa station, which was the highest SAT after 1979/80 summer. The lower tropospheric warming is mainly due to foehn in down-slope wind which was a branch of atmospheric circulation around a low system centered to the northeast of Syowa station. Analyses of upper air data observed by radiosondes at Syowa station and numerical simulation results by WRF showed that the latter event is more plausible to form the phenomenon of scattering of ice-pieces by surface melting though we cannot specify the event absolutely from the two candidates because there were no in-situ observation. However, such analyses of the two extreme events occurred in 2012/13 summer are valuable in terms of mechanism of melting or modification of Antarctic ice-sheet surface. Thus, this paper demonstrates the two synoptic-scale events with the meteorological elements observed at Syowa station, satellite data, and results obtained from numerical simulation using WRF. This paper also attempts to discuss long-term variation in SAT at Syowa station in connection with the long-term evolution of Ozone Hole. Polar Meteorology and Glaciology Group seminar / 気水圏コロキウム 日時：4月20日（水）10:00-10:50 場所：C301（3階セミナー室） conference object